Evaluation of Rural Tourism Concept for Cultural Preservation (Case Study of Baduy Tribe Rejecting Tourism) - Pradana, Triandi; Widyawan, Indria; Sanjaya, Yoel (Ilomata International Journal of Social Science, 2025)
The customary leaders of the Baduy community previously expressed the rejection of Baduy as a tourist attraction. Given the increasing number of tourist visits and the growing prominence of Baduy Rural Tourism, there are concerns that this could lead to over-tourism and negatively impact tourist activities. This research aims to evaluate the concept of Baduy cultural rural tourism, addressing the issues surrounding the community's rejection of tourism as a development model. The objectives of this research are: 1) to understand the implementation of the tourist village concept; 2) to identify the challenges faced by tourism activities; and 3) to explore potential evaluation and improvement strategies. Using a qualitative approach with a case study and Miles and Huberman's interactive analysis. Selection of 10 informants with relevant characteristics, including one key informant, the customary leader who possesses knowledge of the traditions and regulations in Baduy; additionally, four informants represent local guides. Two informants are Baduy residents. Three informants represent tourists. Tourism indirectly impacts the social and cultural life of the Baduy community. Although Kanekes Village enforces strict regulations under Village Regulation regarding Cultural Saba and the Protection of Baduy Indigenous People, implementing these rules requires further evaluation and monitoring.